Large Magnetoresistance in Magnetically Coupled SrRuO3 –CoFe2O4 Self‐Assembled Nanostructures. (12th July 2013) - Liu, Heng‐Jui; Tra, Vu‐Thanh; Chen, Ying‐Jiun; Huang, Rong; Duan, Chun‐Gang; Hsieh, Ying‐Hui; Lin, Hong‐Ji; Lin, Jiunn‐Yuan; Chen, Chien‐Te; Ikuhara, Yuichi; Chu, Ying‐Hao
<x xml:space="preserve">Abstract</x> A new way to induce a large magnetoresistance has been achieved by self‐assembled nanostructures consisting of ferromagnetic spinel CoFe2O4 (CFO) and metallic perovskite SrRuO3 (SRO). The interdiffused Fe3+ ions in SRO have paved the way to strong magnetic couplings with CFO nanopillars, resulting in the suppression of spin‐polarized electron scattering. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>